The importance of physiological traits in association with metabolism in the development of speed endurance among middle distance runners - Meziane, B.; Bachir, K.; Fatah, M.; Dahma Tarik, K. B. (European Journal of Physical Education and Sport Science, 2016)
This study sets up to investigate the importance of physiological traits in relation to metabolism in the development of speed endurance among runners at middle-distances. It aims at determining the level of physiological traits which are associated with metabolism among runners; in addition of developing the required physical attributes especially speed endurance. Accordingly, the researchers have administered two main physiological tests: The River index test and the Shannon flash back heart curve test to a sample of 15 runners from the athletics games club of Blida (Algeria). Their age range varies between 17 and 18 years